Understanding Tourists’ Environmental Responsibility: Testing a Behavioral Model in the Thousand Islands from a Quality Tourism Perspective - Ginta Ginting; Anisa Zahwa Akbara; Yulita Suryantati; Sri Ismulyati (Yayasan Sinergi Kawula Muda, 2026)
Tourism destinations increasingly face environmental pressures resulting from growing visitor numbers, particularly in island destinations where ecological resources are highly vulnerable. Within the quality tourism paradigm, tourists are expected to act not only as consumers but also as responsible environmental stakeholders. This study empirically examines the relationships among place dependence, place identity, environmental knowledge, destination social responsibility (DSR), personal norms, and environmentally responsible behavior (ERB) among visitors to the Thousand Islands, Indonesia. A cross-sectional survey was conducted with 310 tourists and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that place dependence, place identity, environmental knowledge, destination social responsibility, and personal norms all positively influence ERB, with environmental knowledge emerging as the strongest predictor. The model demonstrates substantial explanatory power (R² = 0.80). Regarding moderation effects, DSR does not significantly strengthen the relationship between place dependence and ERB, while its interaction with place identity is significant but negative, suggesting that strong emotional attachment may reduce reliance on external sustainability cues. Personal norms do not significantly moderate the relationship between environmental knowledge and ERB. By integrating established constructs from place attachment, norm activation, and sustainable tourism research within a quality tourism framework, this study contributes to understanding how cognitive, emotional, and moral factors jointly shape environmentally responsible behavior among tourists. The findings offer practical implications for destination managers seeking to encourage sustainable visitor behavior through environmental education, place-based experiences, and visible sustainability initiatives.